CITOGENÉTICA MOLECULAR EM Characidium: UMA ANÁLISE DA DIVERSIFICAÇÃO DOS CROMOSSOMOS SEXUAIS ZZ/ZW - Machado, Tatiana Cristina (2011)
The Characidium genus shows a broad karyotypic variability regarding the origin and diversification of the sex chromosomes, intra-and interindividual variation of B chromosomes and location of sites and number of NORs chromosomes bearing. Variations in the sex chromosomes Z and W morphology provide an excellent model to study chromosomal differentiation associated with a potential mechanism for reproductive isolation. In this study, we obtained a probe of the sex chromosome W of Characidium gomesi by chromosome microdissection , amplification by DOP-PCR and conducting comparative chromosome painting of W probe together with the 18S rDNA probe in some populations / species: C. gomesi of Rio Verde (PR), C. gomesi of Rio Grande (SP), C. gomesi of Ribeirão Minhoca (MG), C. lauroi of the Rio Grande (SP), C. zebra of Passa Cinco (SP). The conventional analysis of the populations of C. gomesi from rio Verde and ribeirão Minhoca, not yet described, showed the diploid number with 50 chromosomes and the presence of sex chromosome ZZ / ZW in advanced stages of differentiation. With the use of dual FISH, W and 18S rDNA probes, in populations of C. gomesi, C. lauroi and C. zebra was hypothesized a pathway of differentiation of sex chromosomes in the group. In this possible pathway, transposition / translocation of the NORs sites to proto sex chromosome was the first event this differentiation. Thereafter, the heterochromatization of other repetitive DNAs, not present in NORs site, acted on the alteration of the chromosomes Z and W morphologies. The heterochromatization of W chromosome wasintense in C. gomesi and C. alipioi species so the NOR siteswere again transposed to an autosomal condition. Was discussed also the biogeographic barriers help to differentiation of sex chromosomes in Characidium promoting reproductive isolation and speciation of the group.